Carrier dynamics in the coupled structure of InGaAs quantum dots in a well - Park, YM; Yoo, KH; Park, YJ; Kim, KM; Song, JD; Lee, JI (KOREAN PHYSICAL SOC, 2004)
We investigated the carrier transfer mechanism in the coupled structure of an InGaAs dots-in-a-well (DWELL). The quantum dots (QDs) were formed by the atomic layer epitaxy (ALE) technique with various cycles of InAs/GaAs alternate source supply. From PL measurements, it was found that DWELL structure was accomplished through the process of generation of an intermediate layer between the quantum well (QW) and the QDs during the formation of QDs in a QW. By controlling the number of cycles of InAs/GaAs alternate source supply, we obtained a unique structure in which InGaAs QW contained the InGaAs QDs and the additional intermediate layer. The temperature dependence of the PL fitted well with the rate equation model for carrier dynamics, in which radiative recombination, carrier thermal escape and a carrier capture process occurred in these three layers, i.e. QW, QD and the intermediate layer.
Keywords: 1.3 MU-M; PHOTOLUMINESCENCE; LASERS